The Effect of Participation and Community Supervision on the Village Fund Planning Process with Office Accountability as a Moderating Variable - Andi Fathatul Khair; Rudy Usman; Jurana Jurana; Rahma Masdar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of Community Participation and Community Oversight on the Village Fund Planning Process, as well as to test the conditional role of Official Accountability as a moderating variable. Using a quantitative method using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to data collected from Officials and community representatives in Dolo Barat District, the results of the study confirm that both Participation and Community Oversight directly contribute significantly to improving planning quality. The most important finding is the complex role of Official Accountability; on the one hand, official accountability strengthens the positive relationship between Community Participation and Planning, indicating optimal goal alignment between responsive officials and active communities. However, on the other hand, Official Accountability actually significantly weakens the positive influence of Community Oversight on Planning. This paradoxical effect indicates that a high level of accountability in Officials can trigger passive behavior or excessive trust from the community (Principals), thereby reducing the intensity and efficacy of the oversight function, which ultimately makes Community Oversight less effective as a driver of planning quality. This study concludes that although Official Accountability is needed to optimize Participation, the community needs to maintain a critical and non-passive attitude in supervision so that village development goals can be achieved optimally and sustainably